Proposed Speech Analyses Method Using the Multiwavelet Transform - Al-Khafaji, Baydaa Jaffer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Speech is the first invented way of communication that human used age before the invention of writing. In this paper, proposed method for speech analyses to extract features by using multiwavelet Transform (Repeated Row Preprocessing).The proposed system depends on the Euclidian differences of the coefficients of the multiwavelet Transform to determine the beast features of speech recognition. Each sample value in the reference file is computed by taking the average value of four samples for the same data (four speakers for the same phoneme). The result of the input data to every frame value in the reference file using the Euclidian distance to determine the frame with the minimum distance is said to be the "Best Match". Simulation program using visual basic has been in order to determine final results.